Human Recombinant Lactoferrin Promotes Differentiation and Calcification on MC3T3-E1 Cells - Daichi Nagashima; Yukiko Ishibashi; Sachiko Kawaguchi; Megumi Furukawa; Masahiro Toho; Megumi Ohno; Takeaki Nitto; Nobuo Izumo (MDPI AG, 2022)
Lactoferrin (LF), known to be present in mammalian milk, has been reported to promote the proliferation of osteoblasts and suppress bone resorption by affecting osteoclasts. However, the mechanisms underlying the effects of human sources LF on osteoblast differentiation have not yet been elucidated, and almost studies have used LF from bovine sources. The presented study aimed to characterize the molecular mechanisms of bovine lactoferrin (IF-I) and human recombinant lactoferrin (LF-II) on MC3T3-E1 pre-osteoblast cells. MC3T3-E1 cells were treated with LF, ascorbic acid, and β-glycerophosphate (β-GP). Cell proliferation was analyzed using the MTT assay. Alkaline phosphatase activation and osteopontin expression levels were evaluated via cell staining and immunocytochemistry. The differentiation markers were examined using quantitative real-time PCR. The cell viability assay showed the treatment of 100 μg/mL LF significantly increased; however, it was suppressed by the simultaneous treatment of ascorbic acid and β-GP. Alizarin red staining showed that the 100 μg/mL treatment of LF enhanced calcification. Quantitative real-time PCR showed a significant increase in osterix expression. The results suggest that treatment with both LFs enhanced MC3T3-E1 cell differentiation and promoted calcification. The mechanisms of calcification suggest that LFs are affected by an increase in osterix and osteocalcin mRNA levels.